STUDENTS’ BEHAVIOR PROBLEMS AND TEACHERS’ COMPETENCIES IN PHYSICAL EDUCATION - Caminos, Israeli S (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 11 No. 1-2, 2008, 2008)
This study determined the degree of seriousness of the students’ behavioral problems in P. E. classes as reported by the students themselves and the level of teachers’ competency as perceived by the students from the two colleges in Camotes Islands, Cebu, Philippines for the school year 2007-2008. It sought further the following: Profile of Teachers, Profile of Students, and the significant relationship between the degree of seriousness of the students’ behavioral problems and the level of teachers’ competency. The degree of seriousness of the behavioral problems of students is found to be Not Serious which means that problems were not at all observed in the students. The level of competency of teachers is Above Average to the four areas and only Instruction is found to be Satisfactory. There was no significant relationship between the students’ behavior problems and the teachers’ competency in Physical Education. Behavioral problems were not at all observed in the P. E. 4 students. Teachers are good to some areas of competencies but have weaknesses in some areas. However, the relationship between the degree of seriousness of the behavioral problems of the students and the level of competency of teachers is not statistically significant.